Pesquisa em educação inclusiva : representações dos docentes das salas de recursos multifuncionais sobre o professor-pesquisador - Barbosa, Eline Freitas Brandão (2017)
Research is a investigation work, a relationship between teaching and practice, resulting in the final product of knowledge production. The research exercise is important to guide the actions of the teacher, because the experiences that he will have through this, since his initial formation, will development a reflexive posture that aims to welcome the diversity and value the individuality of the subjects. This study aimed to analyze the representation of the researcher-teacher by teachers of the elementary school of the public school system in the State of Sergipe who working in Multifuncional Feature Rooms, as well as to analyze the construction of the knowledge produced in their practice through action of the research. As methodological procedure for obtaining data, we carried out a qualitative investigation based on Discourse Analysis, where we used as instrument a semi-structured interview. The results were organized according to the following categories: teacher training, researcher-teacher and research in inclusive education. We conclude that there is a gap between the majority of the research practices developed by the teachers in the classroom, which result in the students' learning, when compared to the training received by the teachers in the undergraduate course.We highlight the research as a vehicle for the development of the knowledge, contributing to the change in behavior and the transformation of the teaching practice itself. In this way, the research extends beyond simply the action of studying, because it is an action inherent to teaching practice that add the organization of knowledge and necessary rigor to the investigative process which is the teaching activity itself.